INFORMATION ACQUISITION METHODS AND THEIR RELATION TO THE LEVEL OF EQUIPMENT OF A FARM IN INFORMATIVE INFRASTRUCTURE ELEMENTS - Kuboń, Maciek; Kwaśniewski, Dariusz; Malaga-Toboła, Urszula; Niemiec, Marcin; Ovcharuk, Oleg; Kocira, Sławomir (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
All item flows are always accompanied by information flows. The condition of the goods flow between a sending point and a receipt point is exchange of information between a sender and a consignee. The role of scientific-technical and economic information in modern agriculture grows successively. It is hard to imagine efficient management that would guarantee rational use of the factors of production, including respect for the environment, ensuring high quality of products and satisfaction of market requirements without it. Information is indispensable for both agricultural producers as well as producers and providers of production means and agricultural products consignees. Farms which strive to be competitive and which want to develop must use facilities of modern information technologies. The aim of the paper was to determine information acquisition methods and the relation to the level of equipment and the use of information infrastructure elements on commodity farms. The paper covered 50 agricultural farms located in the south Poland region. Information acquisition methods and the level of equipment and use of information infrastructure elements were determined. Respondents also evaluated which of the information acquisition methods was the best and which was the worst. It was concluded that the level of farm equipment in elements of information infrastructure was satisfactory and the information infrastructure methods guaranteed efficient farm management.